if 3 + under root 7 divided by 3 minus under root 7 is equal to a + b under root 7 then( a, b) is equal to
Answers
Answered by
2
Solution:-
![\frac{3 + \sqrt{7} }{3 - \sqrt{7} } = a + b \sqrt{7} \\ by \: lhs \\ \frac{3 + \sqrt{7} }{3 - \sqrt{7} } \times \frac{ 3 + \sqrt{7} }{3 + \sqrt{7} } \\ \frac{9 + 7 + 6 \sqrt{7} }{9 - 7} \\ \frac{16 + 6 \sqrt{7} }{ 2} \\ {8 + 3 \sqrt{7} } = a + b \sqrt{7} \\ a = 8 \\ b = 3 \frac{3 + \sqrt{7} }{3 - \sqrt{7} } = a + b \sqrt{7} \\ by \: lhs \\ \frac{3 + \sqrt{7} }{3 - \sqrt{7} } \times \frac{ 3 + \sqrt{7} }{3 + \sqrt{7} } \\ \frac{9 + 7 + 6 \sqrt{7} }{9 - 7} \\ \frac{16 + 6 \sqrt{7} }{ 2} \\ {8 + 3 \sqrt{7} } = a + b \sqrt{7} \\ a = 8 \\ b = 3](https://tex.z-dn.net/?f=+%5Cfrac%7B3+%2B++%5Csqrt%7B7%7D+%7D%7B3+-++%5Csqrt%7B7%7D+%7D++%3D+a+%2B+b+%5Csqrt%7B7%7D++%5C%5C+by+%5C%3A+lhs+%5C%5C+%5Cfrac%7B3+%2B++%5Csqrt%7B7%7D+%7D%7B3+-++%5Csqrt%7B7%7D+%7D++%5Ctimes++%5Cfrac%7B+3+%2B++%5Csqrt%7B7%7D++%7D%7B3+%2B++%5Csqrt%7B7%7D+%7D++%5C%5C++%5Cfrac%7B9+%2B+7+%2B+6+%5Csqrt%7B7%7D+%7D%7B9+-+7%7D++%5C%5C++%5Cfrac%7B16+%2B+6+%5Csqrt%7B7%7D+%7D%7B+2%7D++%5C%5C++%7B8+%2B+3+%5Csqrt%7B7%7D+%7D+%3D+a+%2B+b+%5Csqrt%7B7%7D++%5C%5C+a+%3D+8+%5C%5C+b+%3D+3)
Similar questions